2018
DOI: 10.1038/s41586-018-0050-1
|View full text |Cite
|
Sign up to set email alerts
|

SAMHD1 acts at stalled replication forks to prevent interferon induction

Abstract: SAMHD1 was previously characterized as a dNTPase that protects cells from viral infections. Mutations in SAMHD1 are implicated in cancer development and in a severe congenital inflammatory disease known as Aicardi-Goutières syndrome. The mechanism by which SAMHD1 protects against cancer and chronic inflammation is unknown. Here we show that SAMHD1 promotes degradation of nascent DNA at stalled replication forks in human cell lines by stimulating the exonuclease activity of MRE11. This function activates the AT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
404
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 362 publications
(433 citation statements)
references
References 59 publications
28
404
1
Order By: Relevance
“…We previously showed that SAMHD1 expression in normal human fibroblasts changes with their proliferation state. 11 The latter function of SAMHD1 permits the degradation of ssDNA stretches removed from the stalled forks preventing accumulation of ssDNA in the cytosol and induction of the interferon response. 8 During S phase CDK-cyclin complexes phosphorylate SAMHD1 at T592 with still debated functional implications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously showed that SAMHD1 expression in normal human fibroblasts changes with their proliferation state. 11 The latter function of SAMHD1 permits the degradation of ssDNA stretches removed from the stalled forks preventing accumulation of ssDNA in the cytosol and induction of the interferon response. 8 During S phase CDK-cyclin complexes phosphorylate SAMHD1 at T592 with still debated functional implications.…”
Section: Introductionmentioning
confidence: 99%
“…8 The protein accumulates in G0/G1 and quiescent cell states, which suggested that the enzyme may exert its activity mainly outside S phase. 11 Genetic defects in SAMHD1 cause human pathologies linked to either of the two recognized functions of the protein, that is, as a dNTP pool regulator and a defense against inflammatory response. At first, T592 phosphorylation was interpreted as a mechanism to inactivate or downregulate SAMHD1 triphosphohydrolase activity.…”
Section: Introductionmentioning
confidence: 99%
“…AGS patients with SAMHD1 mutations do not display an accumulation of rNMPs (Lim et al, 2015), but the activation of an IFN response is similarly evoked by cGAS-STING-mediated sensing of endogenous DNA species in the cytoplasm (Coquel et al, 2018). AGS patients with SAMHD1 mutations do not display an accumulation of rNMPs (Lim et al, 2015), but the activation of an IFN response is similarly evoked by cGAS-STING-mediated sensing of endogenous DNA species in the cytoplasm (Coquel et al, 2018).…”
Section: Compromised Rer Causes Aicardi-goutières Syndromementioning
confidence: 99%
“…A recent study using SAMHD1-deficent mice showed these mice lack autoimmune phenotypes but are hyperactive in cGAS/STING signaling and induce the expression of type I IFN genes Ifit1 and Ifi44 (Behrendt et al, 2013; Maelfait et al, 2016). Additionally, SAMHD1 has also been implicated in DNA damage responses through its ability to maintain genome stability, digest ssDNA fragments at stalling replication forks, and inhibiting a cGAS/STING inflammatory response (Coquel et al, 2018; Kretschmer et al, 2015; Medeiros et al, 2018). A recent study has shown that SAMHD1 can suppress innate immune induction independently of its dNTPase activity.…”
Section: Intracellular Recognition Of Dnamentioning
confidence: 99%